Penguatan Kapasitas Kelembagaan Petani Melalui Bank Pakan Sebagai Unit Produksi di Kelompok Tani Mekarsari Kecamatan Gandusari Kabupaten Blitar - Sad Likah, Sad Likah (Jurnal KIRANA, 2024)
ABSTRACT One of the efforts to strengthen the capacity of farmer groups is through the establishment of a Feed Bank production unit managed by the Mekarsari group. This research aims to: 1) formulate the design of animal feed innovation counseling to strengthen the production unit of the Feed Bank, and 2) describe the evaluation of counseling on the production of animal feed innovations for members of the Mekarsari Farmers Group. The method used was Participatory Action Research (PAR) with the research location in Mekarsari Farmer Group, Gadungan Village, Gandusari District, Blitar Regency. The questionnaire was prepared using a Likert Scale and data analysis was carried out using quantitative descriptive methods. Respondents consisted of 28 farmers who are members of the Mekarsari III Farmer Group. The product that has been produced in the Mekarsari Feed Bank production unit is complete feed silage with a production of 10 tons per month, with marketing reach limited to members. Product diversification is needed to improve the function of the feed bank business unit. Feed technology innovations that need to be introduced include: 1) fermentation of complete feed based on local feed ingredients, 2) making feed biscuits, and 3) promotion through social media. The results showed that the extension of fermented feed innovation, through lectures, discussions, and hands-on practice, succeeded in getting a positive attitude from 53.33% of farmers and very positive from 46.67% of farmers towards the use of corn cobs. Evaluation of the biscuit feed innovation showed that 80% of farmers had high knowledge of making goat feed biscuits. The increase in knowledge and marketing skills through social media was also significant, with an increase in knowledge by 47.57% and skills by 40%.